Fibrochondrogenesis of hESCs: Growth Factor Combinations and Cocultures - Hoben, Gwendolyn M. (Mary Ann Liebert, Inc., 2009)
The successful differentiation of human embryonic stem cells (hESCs) to fibrochondrocyte-like cells and characterization of these differentiated cells is a critical step toward tissue engineering of musculoskeletal fibrocartilages (e.g., knee meniscus, temporomandibular joint disc, and intervertebral disc). In this study, growth factors and primary cell cocultures were applied to hESC embryoid bodies (EBs) for 3 weeks and evaluated for their effect on the synthesis of critical fibrocartilage matrix components: glycosaminoglycans (GAG) and collagens (types I, II, and VI). Changes in surface markers (CD105, CD44, SSEA, PDGFRα) after the differentiation treatments were also analyzed. The study was conducted in three phases: (1) examination of growth factors (TGF-β3, BMP-2, BMP-4, BMP-6, PDGF-BB, sonic hedgehog protein); (2) comparison of two cocultures (primary chondrocytes or fibrochondrocytes); and (3) the combination of the most effective growth factor and coculture regimen. TGF-β3 with BMP-4 yielded EBs positive for collagens I, II, and VI, with up to 6.7- and 4.8-fold increases in GAG and collagen, respectively. Analysis of cell surface markers showed a significant increase in CD44 with the TGF-β3 + BMP-4 treatment compared to the controls. Coculture with fibrochondrocytes resulted in up to a 9.8-fold increase in collagen II production. The combination of the growth factors BMP-4 + TGF-β3 with the fibrochondrocyte coculture led to an increase in cell proliferation and GAG production compared to either treatment alone. This study determined two powerful treatments for inducing fibrocartilaginous differentiation of hESCs and provides a foundation for using flow cytometry to purify these differentiated cells.